A Phase I trial to evaluate the safety and immunogenicity of WRSs2 and WRSs3; two live oral candidate vaccines against Shigella sonnei. Issue 32 (6th August 2018) - Frenck, Robert W; Baqar, Shahida; Alexander, William; Dickey, Michelle; McNeal, Monica; El-Khorazaty, Jill; Baughman, Holly; Hoeper, Amy; Barnoy, Shoshana; Suvarnapunya, Akamol E.; Kaminski, Robert W.; Venkatesan, Malabi M.
Highlights: Shigella is a significant cause of morbidity and mortality among children in the developing world and travelers to endemic areas. There are no licensed vaccines against Shigella. The study showed the safety and immunogenicity of two live-attenuated, oral S. sonnei vaccines. Future research will evaluate the efficacy of the vaccines against S. sonnei infection in a human challenge model. Abstract: Effective vaccines are needed to combat diarrheal diseases due to Shigella . Two live oral S. sonnei vaccine candidates, WRSs2 and WRSs3, attenuated principally by the lack of spreading ability, as well as the loss of enterotoxin and acyl transferase genes, were tested for safety and immunogenicity. Healthy adults 18–45 years of age, assigned to 5 cohorts of 18 subjects each (WRSs2 (n = 8), WRSs3 (n = 8) or placebo (n = 2)) were housed in an inpatient facility and administered a single oral dose of study agent 5 min after ingestion of oral bicarbonate. Ascending dosages of vaccine (from 10 3 CFU to 10 7 CFU) were evaluated. On day 8, treatment with ciprofloxacin (500 mg BID for 3 days) was initiated and subjects were discharged home 2 days after completing antibiotics. Subjects returned for outpatient visits on day 14, 28 and 56 post-vaccination for monitoring and collection of stool and blood samples. Both WRSs2 and WRSs3 were generally well tolerated and safe over the entire dose range. Among the 80 vaccinees, 11 subjects developed diarrhea, 8 of which were mild and did not affect daily activities. At the 10 7 CFU dose, moderate diarrhea occurred in one WRSs2 subject while at the same dose of WRSs3, 2 subjects had moderate or severe diarrhea. Vaccinees mounted dose-dependent mucosal and systemic immune responses that appeared to correlate with fecal shedding. S. sonnei vaccine candidates WRSs2 and WRSs3 are safe and immunogenic over a wide dose range. Future steps will be to select the most promising candidate and move to human challenge models for efficacy of the vaccine.